2022
DOI: 10.33225/pec/22.80.273
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Experiences of the Transition From Analogue to Digital Learning During the Covid-19 Pandemic

Abstract: The transition from analogue campus-based learning to digital distance learning during the Covid-19 pandemic affected our society in many ways. This study set out to explore the experiences of 30 pre-service teachers when transitioning to digital distance learning. The pre-service teachers (PSTs) participated in a series of focus-group interviews that were subsequently analysed using qualitative content analysis. The results indicate that the transition to digital distance learning worked well and that the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As a final point regarding the effects of the experience of lockdown, although these findings are only cross-sectional rather than longitudinal and are thus limited in their interpretation (see Section 6 for further discussion), they present initial evidence suggesting that preservice teachers may have drawn some benefits for their technology-related knowledge from the experience of remote learning. Several further studies report similar findings of the experience of lockdown to have been an opportunity for both inservice (e.g., DeCoito & Estaiteyeh, 2022 ) as well as preservice teachers (e.g., Bäcklund et al, 2022 ; Elçiçek, 2021 ) to extend their knowledge of technological tools and resources, as well as being forced to develop new designs and approaches in their teaching. Taken together, evidence presents the experience of lockdown as an event giving rise to a period effect (i.e., experience similarly affecting all groups within a population; see Altman, 2014 ) and thus of relevance for comparative research as well as for the professional development of preservice and inservice teachers having experienced lockdowns.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…As a final point regarding the effects of the experience of lockdown, although these findings are only cross-sectional rather than longitudinal and are thus limited in their interpretation (see Section 6 for further discussion), they present initial evidence suggesting that preservice teachers may have drawn some benefits for their technology-related knowledge from the experience of remote learning. Several further studies report similar findings of the experience of lockdown to have been an opportunity for both inservice (e.g., DeCoito & Estaiteyeh, 2022 ) as well as preservice teachers (e.g., Bäcklund et al, 2022 ; Elçiçek, 2021 ) to extend their knowledge of technological tools and resources, as well as being forced to develop new designs and approaches in their teaching. Taken together, evidence presents the experience of lockdown as an event giving rise to a period effect (i.e., experience similarly affecting all groups within a population; see Altman, 2014 ) and thus of relevance for comparative research as well as for the professional development of preservice and inservice teachers having experienced lockdowns.…”
Section: Discussionmentioning
confidence: 76%
“…This led them to experience remote education from both sides of the coin. From both these perspectives, initial studies find mixed outcomes of preservice teachers reporting both negative as well as positive views towards remote education (e.g., Bäcklund et al, 2022 ; Elçiçek, 2021 ; Erumit et al, 2021 ). With regard to their experiences as remote learners, multiple studies found negative views to be associated with recurring challenges of unreliable or complete lack of infrastructure (Erumit et al, 2021 ; Mohamad Nasri et al, 2020 ; Naah, 2020 ) as well as a lack of motivation (Erumit et al, 2021 ) and social interaction (Bäcklund et al, 2022 ).…”
Section: Overview Of the Current Literaturementioning
confidence: 99%
See 3 more Smart Citations